What Questions Are on the Minds of STEM Undergraduate Students and How Can They Be Addressed? - Meaders, Clara L.; Smith, Michelle K.; Boester, Timothy; Bracy, Anne; Couch, Brian A.; Drake, Abby G.; Farooq, Saima; Khoda, Bashir; Kinsland, Cynthia; Lane, A. Kelly; Lindahl, Sarah E.; Livingston, William H.; et al. (Frontiers in Education, 2021)
Addressing common student questions in introductory STEM courses early in the term is one way that instructors can ensure that their students have all been presented with information about how to succeed in their courses. However, categorizing student questions and identifying evidence-based resources to address student questions takes time, and instructors may not be able to easily collect and respond to student questions at the beginning of every course. To help faculty effectively anticipate and respond to student questions, we 1) administered surveys in multiple STEM courses to identify common student questions, 2) conducted a qualitative analysis to determine categories of student questions (e.g., what are best practices for studying, how can in- and out-of- course time be effectively used), and 3) collaboratively identified advice on how course instructors can answer these questions. Here, we share tips, evidence-based strategies, and resources from faculty that instructors can use to develop their own responses for students. We hope that educators can use these common student questions as a starting point to proactively address questions throughout the course and that the compiled resources will allow instructors to easily find materials that can be considered for their own courses.